Is there a link between progranulin, obesity, and parameters of the metabolic syndrome in children? Findings from a longitudinal intervention study. Issue 8 (18th September 2019) - Niklowitz, Petra; Rothermel, Juliane; Lass, Nina; Barth, Andre; Reinehr, Thomas
Abstract: Background: The inflammatory cytokine progranulin has been proposed to play a role in obesity and its associated comorbidities such as insulin resistance. Objective: In a longitudinal study, we analyzed the links between progranulin, parameters of fat mass, insulin resistance, and metabolic syndrome (MetS) in obese children. Methods: We measured the following parameters in 88 obese children at baseline, at the end of a 1‐year lifestyle intervention and 1‐year later (=2 years after baseline): progranulin, bioactive leptin, body mass index‐SD score (BMI‐SDS), waist circumference, body fat based on skinfold measurements and bioimpedance analyses, lipids, transaminases, insulin resistance index homeostasis model assessment (HOMA), and blood pressure. As a control, we determined progranulin in 23 normal‐weight children. Results: The progranulin concentrations did not differ significantly ( P = .795) between obese and normal‐weight children. Progranulin concentrations decreased significantly during and after the lifestyle intervention in children with and without decrease of BMI‐SDS. There was no relationship between progranulin concentrations and pubertal stage or gender. Progranulin was not significantly associated with insulin resistance HOMA, parameters of the MetS or transaminases both in cross‐sectional and longitudinal multiple linear regression analyses adjusted to multiple confounders. Progranulin was significantly, negatively related to age (b‐coefficient −1.24 ± .97, P = .012, r 2 = .07). Conclusions: Our data do not support the hypothesis that progranulin is an important link between obesity, insulin resistance, and MetS in childhood.